BIM Capabilities to Achieve Projects Key Performance Indicators in Kingdom of Saudi Arabia Infrastructure Projects - Hussain, Sharafat; Hasmori, Muhammad Fikri; Khan, Muhammad Wajidullah; Said, Ilias (International Journal of Sustainable Construction Engineering and Technology, 2024)
The construction industry in Saudi Arabia is experiencing significant expansion as a result of governmental initiatives and international construction firms’ investments. The utilisation of conventional approaches proved inadequate in achieving the demands of the contemporary era, leading to the failure to attain project key performance indicators (KPIs) and project success, subsequent project delays, cost overrun, and time overrun. The present study focuses on the implementation of BIM in infrastructure construction projects within the context of KSA and BIM has the potential to assist in achieving project KPIs. The objective of this research is to prioritize Building Information Modelling (BIM) applications towards project key performance indicators (KPIs) with the implementation of Fuzzy AHP to manage and achieve project success in the Kingdom of Saudi Arabia (KSA). To do this, a review of the literature on the KPIs and associated BIM contributions was conducted. A novel feature of the methodology employed by the researcher is the application of the Delphi method and the Fuzzy Analytic Hierarchy Process (FAHP). During the initial phases of the study, professionals offered multiple rounds of input and feedback utilizing the Delphi method. In the third round, a consensus was reached. Subsequently, an enhanced fuzzy AHP was employed to establish a correlation between KPIs of a project and BIM capabilities. The study revealed that the utilization of BIM software for infrastructure projects can facilitate that clash detection, cost estimation, and construction monitoring play a significant role in the successful implementation of BIM and can help reduce costs, save time, and improve quality during construction by detecting potential conflicts and errors early in the design phase. Additionally, the utilization of 4D, which involves project scheduling and construction sequencing, and 5D, which involves construction cost estimation, has subsequent positive impacts on the KPIs of infrastructure construction projects in KSA.